Неизвестная заметка Ю. М. Лотмана [An Unknown Juri Lotman’s Note] - Utgof, Grigori (Slavica Revalensia, 2022)
This is a prefaced publication of Juri Lotman’s brief note “Lenin in Mayakovsky’s Poems and Eisenstein’s Art,” which he wrote for his student in the Spring of 1970, and softly encouraged to publish under her name in Materialy XXV nauchnoi konferentsii molodykh filologov (Proceedings of 25th Junior Scholar Conference).